Factors associated with early weaning in babies seen at a health unit in southern Brazil (Research, Society and Development, 2020)
Breastfeeding in early life has many benefits, ensuring optimum conditions of nutrition and development of different systems of the infant, and benefits to the mother. When feeding to the breast is interrupted early, for different reasons, the child may acquire deleterious oral habits, such as the use of a pacifier. The objective of this study was to investigate a possible association between early weaning and deleterious oral habits (pacifiers, digital suction, bottle feeding) in a group of individuals. It is an exploratory, observational, descriptive, quantitative study. Secondary data were collected from 360 records of children from 0 to 2 years of age who entered the Baby Clinic Program of a Basic Health Unit (Brazil), from July 2015 to July 2017. The data were tabulated and analyzed in the Microsoft Excel Program, using descriptive statistics, using the absolute and percentage frequencies, using the chi-square test, significance level of 5%. The results showed no significant association between early weaning and maternal age, schooling, type of delivery, mother's work, income and marital status. Regarding the deleterious habits, there was a significant association (p = 0.00) between a shorter period of breastfeeding and acquisition of the pacifier habit. Also, the use of bottle feeding (p = 0.00) with breastfeeding time, especially up to 6 months, and 7 to 12 months. Thus, this study provides relevant information to the implementation of new guidelines and practices for mothers by health professionals, alerting them to the risk of early weaning.